1992
DOI: 10.1093/geronj/47.3.p180
|View full text |Cite
|
Sign up to set email alerts
|

A Measure of Paradigm Beliefs About the Social World

Abstract: This study examined the reliability and construct validity of, along with age differences in, a measure of paradigm beliefs about the social world, beliefs that have been proposed to develop across the adolescent and adult life span. The scale is a 27-item, forced-choice preference measure of absolute, relativistic, and dialectical paradigm beliefs. In a series of investigations with 445 subjects, ranging in age from 16 to 83 years, it was shown to have good internal consistency and test-retest reliability, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
58
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 0 publications
5
58
0
Order By: Relevance
“…In addition, most of the study populations in the Berlin Wisdom Project were well-educated adults, which could have restricted the likelihood of detecting individual differences in wisdom-related reasoning. Moreover, the stimulus materials in the Berlin project consisted of very brief descriptions of personal problems, which provided little contextual information (16-18).Both Basseches (10, 11) and Kramer (12,19,20) also attempted to investigate cognitive processes associated with wisdom and age. They found that some aspects of wise reasoning were positively associated with age.…”
mentioning
confidence: 99%
“…In addition, most of the study populations in the Berlin Wisdom Project were well-educated adults, which could have restricted the likelihood of detecting individual differences in wisdom-related reasoning. Moreover, the stimulus materials in the Berlin project consisted of very brief descriptions of personal problems, which provided little contextual information (16-18).Both Basseches (10, 11) and Kramer (12,19,20) also attempted to investigate cognitive processes associated with wisdom and age. They found that some aspects of wise reasoning were positively associated with age.…”
mentioning
confidence: 99%
“…All participants were un- Belief Inventory (SPBI), developed by Kramer et al (1992). The SPBI scale has shown internal consistencies ranging from .60 to .84 (M = .72; SD = .11).…”
Section: Methodsmentioning
confidence: 99%
“…Each world hypothesis or paradigm consists of a set of ontological, epistemological and anthropological axioms. More recently within the adult cognition literature, Pepper's two analytic world hypotheses of formism and mechanism have been combined into a single mechanistic paradigm (Botella and Gallifa, 1995;Johnson et al, 1988;Kramer et al, 1992). Formism assumes the existence of universal forms or types through which all entities can be classified and understood.…”
Section: Oversight Versus Paradigmatic Differencesmentioning
confidence: 99%
“…The contextualist paradigm can be characterized by a constructivist epistemology in contrast to the positivist epistemology of the mechanistic paradigm (Berzonsky, 1994;Botella and Gallifa, 1995). The integrated contextualist paradigm, akin to relativist and dialectical models (Kramer et al, 1992) and Perry's (1970) contextual relativism, views reality to be unique to each individual's perspective, experience and situation. This view epistemologically asserts that reality is internal to the knower and that the relationship between the knower and reality is subjective and relative.…”
Section: A Contextualist Perspectivementioning
confidence: 99%